2017
DOI: 10.18632/oncotarget.22320
|View full text |Cite
|
Sign up to set email alerts
|

The fate of murine double minute X (MdmX) is dictated by distinct signaling pathways through murine double minute 2 (Mdm2)

Abstract: Mouse double minute 2 (Mdm2) and MdmX dimerize in response to low levels of genotoxic stress to function in a ubiquitinating complex, which signals for destabilization of p53. Under growth conditions, Mdm2 functions as a neddylating ligase, but the importance and extent of MdmX involvement in this process are largely unknown. Here we show that when Mdm2 functions as a neddylating enzyme, MdmX is stabilized. Furthermore, we demonstrate that under growth conditions, MdmX enhances the neddylation activity of Mdm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Using an in vitro neddylation reaction with GST-VHL, His-Mdm2, and His-Src, Mdm2 neddylated VHL, and this activity was enhanced with Src ( Figure 3E ), as previously published [ 16 ]. In accordance with previously published data, the addition of MdmX to this reaction also increased the neddylation of VHL ( Figure S2C ) [ 27 ]. It has been shown that Src is phosphorylated at Y416 in response to hypoxia, and we verified this in our cells ( Figure 3F ) [ 28 ].…”
Section: Resultssupporting
confidence: 92%
“…Using an in vitro neddylation reaction with GST-VHL, His-Mdm2, and His-Src, Mdm2 neddylated VHL, and this activity was enhanced with Src ( Figure 3E ), as previously published [ 16 ]. In accordance with previously published data, the addition of MdmX to this reaction also increased the neddylation of VHL ( Figure S2C ) [ 27 ]. It has been shown that Src is phosphorylated at Y416 in response to hypoxia, and we verified this in our cells ( Figure 3F ) [ 28 ].…”
Section: Resultssupporting
confidence: 92%
“…However, we did not observe any change in its expression upon the neddylation blockade ( Figure 5 A). Pevonedistat can also enhance the ubiquitination activity of MDM2, which has been reported to target both Slug and MDMX [ 23 , 24 ]. Nevertheless, we did not observe any change in MDMX levels in our cells upon MLN4924 treatment ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested E3 ligase FBXO11 as a regulator of Slug degradation upon MLN4924 treatment; however, we did not observe any change in its expression in our cell models. Pevonedistat was also reported to enhance the ubiquitination activity of MDM2, which targets both Slug and MDMX [ 23 , 24 ]. Nevertheless, we did not observe any change in MDMX levels upon the neddylation blockade in our cell models, except in C4-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several evidences suggest that neddylation, promoted by Mdm2, regulates p53 signaling at different levels. Under DNA damage conditions, the phosphorylation of Mdm2 and MdmX by c-Abl promotes the association of the heterodimer, with Mdm2 acting as a ubiquitinating enzyme that destabilizes MdmX resulting in p53 stabilization [82][83][84]. On the contrary, in growing conditions under c-Src activity, Mdm2 acts as neddylating enzyme that neddylates p53, Mdm2 itself, and MdmX [84,85].…”
Section: The Mdm2/p53 Pathwaymentioning
confidence: 99%
“…Under DNA damage conditions, the phosphorylation of Mdm2 and MdmX by c-Abl promotes the association of the heterodimer, with Mdm2 acting as a ubiquitinating enzyme that destabilizes MdmX resulting in p53 stabilization [82][83][84]. On the contrary, in growing conditions under c-Src activity, Mdm2 acts as neddylating enzyme that neddylates p53, Mdm2 itself, and MdmX [84,85]. Neddylation of p53 prevents the nuclear translocation and inhibits p53 transcriptional activity; in contrast the neddylation-resistant mutants retain the transcriptional activity [59].…”
Section: The Mdm2/p53 Pathwaymentioning
confidence: 99%